ADVERTISING AND PR AS TOOLS OF INFLUENCE IN MARKETING OF CREATIVE INDUSTRIES - LYSYTSYA, Nadiya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the use of tools for influencing consumers in the marketing of creative industries. The essence of marketing of creative industries is defined. The main difference is that the marketing of creative industries works not only with rational benefit, but also with emotional value, uniqueness and cultural meaning.  In the creative industries, the main force of influence is emotions, uniqueness, and cultural context. Here, the consumer buys not only a product or service, but also experience, aesthetics, identity. Thus, creative marketing is not just a set of promotion tools, but a whole strategy that combines creativity, cultural value, and business thinking. It is established that the tools of influencing consumers advertising, PR in the marketing of creative industries have not only a commercial, but also an emotional and cultural component. They work at the intersection of economics, culture and psychology. It was found that not only rational benefit is important, but also emotional value, uniqueness and cultural meaning. Creativity is not limited to "beautiful ideas." Creativity is provided by a system of tools of influence, among which advertising and PR play an important role. But marketers face a number of specific difficulties when trying to effectively use advertising and PR as tools for influencing consumers:1}saturation of the information space; 2) subjectivity of perception of creativity; 3)difficulties in measuring efficiency; 4) balance between commerciality and creativity; 5) the fleeting  nature of trends; 6) dependence on the media and opinion leaders; 7) heterogeneity of the target audience; 8) risk of loss of uniqueness; 9) limited budgets. So, advertising provides tools of influence for the vivid presentation of ideas, PR provides context, trust and social significance. Together, they reinforce each other and make the marketing of creative industries alive and influential. In the marketing of creative industries, advertising and PR work as key tools for the formation of demand, image and loyalty. They solve different, but complementary tasks.
Keywords: marketing of creative industries; tools of influence; advertising; PR; emotional value